Investment Performance of Islamic Bank: An Empirical Study - Dooty, Evana Nusrat; Islam, Mohammed Syedul (Asian Business Review, 2015)
The article undertakes an empirical study on investment of Islamic Bank. The aim of the study is to examine and evaluate the performance of investment of Islamic Bank for the time period 2005-2009 in comparison with a conventional Bank. Several financial ratios are applied for this purpose. For the empirical investigation data has been collected from Islami Bank Bangladesh Limited and Mutual Trust Bank Limited. The study found that Islami Bank Bangladesh Limited (IBBL) is relatively less profitable and less risky (more solvent) during 2005-2009 compared to a conventional bank (Mutual Trust Bank Limited), however, it is improving considerably over time indicating convergence with the performance of the conventional banks.